Impact of saline irrigation and topical corticosteroids on the postsurgical sinonasal microbiota. Issue 3 (29th December 2014) - Liu, Cindy M.; Kohanski, Michael A.; Mendiola, Michelle; Soldanova, Katerina; Dwan, Michael G.; Lester, Richard; Nordstrom, Lora; Price, Lance B.; Lane, Andrew P.
<x xml:space="preserve">Abstract</x> Background Topical treatments with nasal saline irrigation, topical steroid sprays, or corticosteroid rinses can improve sinonasal symptoms in chronic rhinosinusitis (CRS). However, the impact of these therapies on commensals (Corynebacterium) and on biofilm pathogens associated with CRS (Staphylococcus aureus and Pseudomonas) is not well characterized. Methods Paired nasal and sinus swabs were collected endoscopically from 28 controls and 14 CRS patients with nasal polyposis (CRSwNP) who had not received systemic antibiotics or corticosteroids in the previous 8 weeks. Total DNA from swab eluents were extracted and analyzed by 16S rRNA gene‐based pyrosequencing. A total of 359, 077 reads were obtained and classified taxonomically. The association of use of topical therapies with sinonasal microbiota composition was assessed by factor/vector‐fitting. The proportional abundances of sinonasal bacteria between topical therapy users and nonusers were further compared by 2‐tailed Kolmogorov‐Smirnov test among controls and among CRSwNP participants. Results Nasal saline irrigation, with or without added budesonide, was not associated with significantly distinct sinonasal microbiota composition or significantly decreased Pseudomonas or S. aureus abundances among either controls or CRSwNP participants. Corynebacterium was slightly lower in controls that reported using saline irrigation than those who did not. No significant association was found between nasal saline irrigation and the proportional abundances of Pseudomonas, S. aureus, and Corynebacterium in CRSwNP participants. However, male CRSwNP patients were noted to have significantly higher Corynebacterium proportional abundances than their female counterparts. The use of topical steroid sprays was associated with a distinct microbiota in control subjects, characterized by higher proportional abundances of Dolosigranulum and Simonsiella and a lower proportional abundance of Campylobacter. Conclusion Nasal saline irrigation is not associated with a distinct alteration in the proportional abundance of commensal bacteria or biofilm‐forming pathogens in CRSwNP patients. However, use of topical intranasal corticosteroid sprays in control subjects is associated with a distinct sinonasal microbiota.